2006
DOI: 10.1097/01.sih.0000244456.22457.e8
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Management Simulation for Children: Translating Theory, Methods, and Strategies to Effect Behavior Change

Abstract: Translating behavioral theories, models, and strategies to guide the development and structure of computer-based health applications is well recognized, although a continued challenge for program developers. A stepped approach to translate behavioral theory in the design of simulations to teach chronic disease management to children is described. This includes the translation steps to: 1) define target behaviors and their determinants, 2) identify theoretical methods to optimize behavioral change, and 3) choos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The majority of the reviewed studies and interventions reported the following key targeted behaviors [ 9 - 13 ]: (1) managing environmental triggers, (2) accessing asthma services, (3) medication adherence, (4) monitoring peak flow regularly by using portable meters, (5) keeping rescue inhaler accessible, and (6) smoke reduction or cessation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the reviewed studies and interventions reported the following key targeted behaviors [ 9 - 13 ]: (1) managing environmental triggers, (2) accessing asthma services, (3) medication adherence, (4) monitoring peak flow regularly by using portable meters, (5) keeping rescue inhaler accessible, and (6) smoke reduction or cessation.…”
Section: Resultsmentioning
confidence: 99%
“…This review has shown that principles, concepts, and strategies of gamification were only applied in four studies. However, these four studies only targeted children up to 12 years old [ 13 - 16 ]. The reviewers could not cite any Internet-based asthma interventions employing gamification concepts for the adolescent or adults’ population groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurse case management can reduce asthma-related emergency care and hospitalization costs, but it is expensive [25,26]. Child-focused, Web-based asthma education and games (eHealth) have improved knowledge, asthma control, and medication adherence in the short run [27-29]. However, parents tend to overestimate their child’s medication-taking skills and actual adherence [30].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions such as CHESS+CM, based on self-determination theory [32] and self-efficacy [33], provide information, social support, and skill-building tools for self-managing the disease. These interventions, which aim to increase confidence, competence, relatedness, and autonomous motivation, have been used successfully in asthma education programs [28,29,32,34]. However, the factors associated with these theories have not been tested for their mediational effects on adherence to controller medications or asthma control.…”
Section: Introductionmentioning
confidence: 99%